Attenuating the forward guidance puzzle: Implications for optimal monetary policy - Taisuke Nakata; Ryota Ogaki; Sebastian Schmidt; Paul Yoo (European Central Bank (ECB), 2019)
We examine the implications of less powerful forward guidance for optimal policy using a sticky-price model with an effective lower bound (ELB) on nominal interest rates as well as a discounted Euler equation and Phillips curve. When the private-sector agents discount future economic conditions more in making their decisions today, an announced cut in future interest rates becomes less effective in stimulating current economic activity. While the implication of such discounting for optimal policy depends on its degree, we find that, under a wide range of plausible degrees of discounting, it is optimal for the central bank to compensate for the reduced effect of a future rate cut by keeping the policy rate at the ELB for longer.
Keywords: E52; E58; E61; 330; Forward Guidance; Optimal Policy; Discounted Euler Equation; Discounted Phillips Curve; Effective Lower Bound